Titanium-Enriched Medium Promotes Environment-Induced Epigenetic Machinery Changes in Human Endothelial Cells - Fernandes, Célio Júnior da C. [UNESP]; da Silva, Rodrigo A. Foganholi; Wood, Patrícia F. [UNESP]; Ferreira, Marcel Rodrigues [UNESP]; de Almeida, Gerson S. [UNESP]; de Moraes, Julia Ferreira [UNESP]; Bezerra, Fábio J. [UNESP]; Zambuzzi, Willian F. [UNESP] (MDPI, 2023)
It is important to understand whether endothelial cells are epigenetically affected by titanium-enriched media when angiogenesis is required during bone development and it is expected to be recapitulated during osseointegration of biomaterials. To better address this issue, titanium-enriched medium was obtained from incubation of titanium discs for up to 24 h as recommended by ISO 10993-5:2016, and further used to expose human umbilical vein endothelial cells (HUVECs) for up to 72 h, when the samples were properly harvested to allow molecular analysis and epigenetics. In general, our data show an important repertoire of epigenetic players in endothelial cells responding to titanium, reinforcing protein related to the metabolism of acetyl and methyl groups, as follows: Histone deacetylases (HDACs) and NAD-dependent deacetylase sirtuin-1 (Sirt1), DNA methyltransferases (DNMTs) and ten-eleven translocation (TET) methylcytosine dioxygenases, which in conjunction culminate in driving chromatin condensation and the methylation profile of DNA strands, respectively. Taking our data into consideration, HDAC6 emerges as important player of this environment-induced epigenetic mechanism in endothelial cells, while Sirt1 is required in response to stimulation of reactive oxygen species (ROS) production, as its modulation is relevant to vasculature surrounding implanted devices. Collectively, all these findings support the hypothesis that titanium keeps the surrounding microenvironment dynamically active and so affects the performance of endothelial cells by modulating epigenetics. Specifically, this study shows the relevance of HDAC6 as a player in this process, possibly correlated with the cytoskeleton rearrangement of those cells. Furthermore, as those enzymes are druggable, it opens new perspectives to consider the use of small molecules to modulate their activities as a biotechnological tool in order to improve angiogenesis and accelerate bone growth with benefits of a fast recovery time for patients.
Keywords: angiogenesis; biological analysis; biomaterial; endothelial cell; epigenetic; titanium